2023
DOI: 10.1002/jad.12145
|View full text |Cite
|
Sign up to set email alerts
|

The role of identity in the development of depressive, anxiety, and psychosis symptoms in adolescents exposed to childhood adversity

Abstract: Introduction: Childhood adversity is a major risk factor for psychiatric disorders and has especially been associated with an admixture of depressive, anxiety, and psychosis symptoms. Identity formation, a main developmental task during adolescence, may be impacted by these adverse experiences and act as an important process in the association between childhood adversity and psychopathology. Methods: We investigated the association between childhood adversity, identity formation, and depressive, anxiety, and p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 70 publications
1
5
0
Order By: Relevance
“…Indeed, in a previous study, we reported a significant association between CA, a more vulnerable identity structure (i.e., synthesis and confusion) and psychopathology. Moreover, a path analysis pointed to identity structure as a potential mediator in the association between CA and psychopathology, though identity structure did not moderate this association (27).…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations
“…Indeed, in a previous study, we reported a significant association between CA, a more vulnerable identity structure (i.e., synthesis and confusion) and psychopathology. Moreover, a path analysis pointed to identity structure as a potential mediator in the association between CA and psychopathology, though identity structure did not moderate this association (27).…”
Section: Introductionmentioning
confidence: 86%
“…Age and sex were added as covariates in all models, and pvalues were adjusted for multiple comparisons using Holm's correction. Finally, in line with (27) within the SIGMA study, we included a path analysis with CA as predictor of the five identity processes and of psychopathology to evaluate the potential mediation effect of identity processes on the association between CA and psychopathology. Although all included analyses are similar to (27), the current study was not preregistered.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…According to identity development theory, those experiencing identity confusion do not have a clear sense of themselves or their role in society (Erikson, 1968) and often report being helpless, dependent on others, and experiencing more negative emotions about how they fit into society (Heinström, 2010; Penner et al, 2019). A study has demonstrated that a reduced sense of self plays a mediating role in the association between childhood maltreatment and a range of adverse mental health outcomes, including depression, perceived stress, and overall distress in life (Samaey et al, 2023). Consequently, adolescents who are confused and uncertain about their identity may experience negative emotions associated with their uncertainty (Zettl et al, 2022).…”
Section: Introductionmentioning
confidence: 99%